Partnership and pragmatism : Germany's response to AIDS prevention and care - Rosenbrock, Rolf, 1945-; Wright, Michael T. (Social aspects of AIDS., 2000)
This book provides a comprehensive overview of the most important themes in German HIV/AIDS prevention and care from the beginning of the epidemic to the present. Multidisciplinary in approach, it highlights the unique contributions of Germany to AIDS work, making available for the first time knowledge which can be applied to other countries as well as to other fields of public health practice. Topics discussed include: *structural prevention, a concept which unites political and behavioural change *the synchronistic relationship between AIDS policy and gay politics *the d.